(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
In a world of ever changing customer expectation, and competitive business environment, building corporative and collaborative relationship with customers seems to be the most prudent way to keep track of their changing expectation and appropriately influencing them. One way in which that some companies are developing an improved focus on Customer Relationship Management (CRM), is through the establishment or consideration of splitting the marketing managers job into two parts: one for acquisition and one for retention. Offensive marketing emphasize on customer acquisition while defensive marketing emphasizes customer retention. The kinds of skills that are needed for people, in acquisition are in the factual aspect of marketing such as advertising, sales while that of retention is on satisfaction, loyalty, customers service, customization, community building and reward program.